Nanoengineering membrane surfaces: A new paradigm for efficient CO2 capture - Leiqing Hu; Vinh T. Bui; Narjes Esmaeili; Haiqing Lin (Carbon Capture Science & Technology, 2024)
Thin-film composite (TFC) membranes with superior separation properties for H2/CO2, CO2/N2, and CO2/CH4 are of great interest for CO2 capture. As the selective layer of the membranes becomes thinner (∼100 nm or less) to enhance gas permeance, it can be surface-engineered to significantly improve gas separation properties. This paper aims to critically review scalable nanotechnologies adopted to modify membrane surfaces to improve CO2 capture performance, including atomic layer deposition, chemical vapor deposition, plasma treatment, direct fluorination, ion/electron beam treatment, ozone treatment, and surface-initiated polymerization. We first describe the mechanisms of these nanotechnologies to achieve desired surface chemistries and nanostructures. Second, examples of surface-modified membranes with enhanced CO2 capture performance are highlighted, and they are compared with state-of-the-art membranes to showcase their potential for gas separations. Finally, we summarize the pros and cons of these technologies to transform membrane technology for practical applications.